L`impact social des grands événements sportifs?: réflexions théoriques et méthodologiques à partir de l`Euro 2016 - Charrier, D.; Jourdan, J.; Bourbillères, H.; Djaballah, M.; Parmantier, C. (Movement & Sport Sciences - Science & Motricité, 2019)
This contribution presents a study of the social impact of UEFA Euro 2016, which was conducted between autumn 2015 and summer 2017. First, the paper shows how the research team has progressively built and tested an analysis framework - based on a succession of studies conducted over the last twenty years - in order to assess the social impact of major sporting events (MSE). Then, it enlightens the diversity, complementarity and productivity of qualitative and quantitative methods deployed before, during and after Euro 2016. Finally, the crossing of empirical results with the literature review leads to the proposal of a definition of MSE`s social impact, thereby inviting debate with scholars and professionals.